Ectopic Expression of Rice OsBIANK1, Encoding an Ankyrin Repeat‐Containing Protein, in Arabidopsis Confers Enhanced Disease Resistance to Botrytis cinerea and Pseudomonas syringae. Issue 1 (26th September 2012) - Li, Dayong; Wang, Fengrang; Liu, Bo; Zhang, Yafen; Huang, Lei; Zhang, Huijuan; Song, Fengming
Abstract Ankyrin repeat‐containing proteins comprise a large family whose members have been shown to play important roles in various aspects of biological processes in plant growth and development as well as in responses to biotic and abiotic stresses. We previously identified a rice gene, OsBIANK1, encoding an ankyrin repeat‐containing protein and found that expression of OsBIANK1 can be induced by defence signalling molecules and by infection of Magnaporthe oryzae, the causal agent of blast disease. To better understand the possible function of OsBIANK1 in disease resistance, we generated transgenic Arabidopsis plants that constitutively overexpress the OsBIANK1 gene. Results from disease assays revealed that the OsBIANK1‐overexpressing plants display increased resistance against Botrytis cinerea and Pseudomonas syringae pv. tomato DC3000 as compared with the wild‐type plants. In OsBIANK1‐overexpressing plants, expression of some of well‐known defence genes (e.g. PR‐1, PR‐2 and PDF1.2) was up‐regulated after infection with B. cinerea or P. syringae pv. tomato DC3000. Furthermore, the OsBIANK1‐overexpressing plants showed decreased levels of reactive oxygen species (i.e. superoxide anion and H2O2) after Botrytis infection. Thus, our present results further support the role of OsBIANK1 in regulation of defence responses against different types of pathogens.